Stigma and vitiligo: the experience of stigma and quality of life in patients with vitiligo - Armon Massoodi; Parsa Halalkhor; Amirmohamad Rezaei Majd; Azar Shirzadian; Faezeh Firuzpour; Hemmat Gholinia; Seyed Gohar Mousavi; Zeinab Aryanian (Discover Social Science and Health)
Abstract Background Vitiligo is a chronic autoimmune skin disease with a prevalence of 0.5–4.0%. Stigma related to this disorder affects different aspects of health in these patients. In this study, we focused on the frequency of stigma in patients with vitiligo, determining the quality of life and the factors affecting them. Methods This cross-sectional study was carried-out on 100 patients with vitiligo referred to the state skin department in north of Iran in 2022. The Feelings of Stigmatization Questionnaire (FSQ), Dermatology Life Quality Index (DLQI) and Vitiligo Area Scoring Index (VASI) questionnaires were used for data collection. Results Mean age of the participants was 30.57 ± 10.14, most of them were women, and residing in urban areas. Most patients had generalized vitiligo, while the second frequent type was acrofacial. The severity of disease was mild in 60% of them. The average score of the FSQ stigma questionnaire was 139.58 ± 24.36, and the average score of the quality-of-life questionnaire was 4.43 ± 4.76. A significant negative correlation was observed between the total score of the stigma experience and the quality of life (r = − 0.579; P < 0.001). Conclusions Vitiligo appears to have a limited impact on the stigma and quality of life perceived by the patients. The study also highlights a negative correlation between stigma status and quality of life in these patients. Therefore, psychological effects of the condition should be considered in management of these individuals with appropriate psychological interventions. Trial registration Not applicable.